The language of perjury cases - Shuy, Roger W. (Oxford : Oxford University Press, 2011)
'The Language of Perjury Cases' outlines the contributions that linguistics can make to both the gathering of evidence and the way that evidence is analyzed in perjury cases.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Perjury -- United States; Forensic linguistics -- United States